PENGARUH PEMBERIAN PAKAN TERHADAP PERTUMBUHAN IKAN KOMET (CARASSIUS AURATUS) DI KABUPATEN BURU: (The Effect of Feeding on the Growth of Comet Fish (Carassius Auratus) In Burus District) - Koto, Saifuddin; Ngofongare, Karmila; Galela, Sakina (Uniqbu Journal of Exact Sciences, 2023)
This study aims to determine the effect of feeding on the growth of Comet fish (Carassius Auratus) in Namlea Village, District. Hurry up. This research was conducted from 31 May to 30 June 2021 in Namlea Village, Namlea District, Buru Regency. The initial test is weighing the weight of the test fish using an analytical balance with an accuracy of 0.0 gram. Fish were stocked in basins of 42 cm each with a density of 3 fish/basin. For the treatment of feed given after the amount of feed given is 3%, 4% and 5% body weight of Comet Fish with a frequency of 3 times a day, namely 08.00, 12.00 and 16.00. Growth measurements are carried out once a week. In this activity aims to determine the growth of the body weight of the test animals. The measurement method is to take the fish with a drain (flour sieve) then place it in a basin containing media water and equipped with aeration, then the fish are taken one by one to be weighed. The highest absolute weight growth was in the P3 treatment with a feed dose of 5% which resulted in an average weight increase of 11.60 grams. The P3 treatment had the highest daily growth rate, which was an average of 7.46 gr, and the lowest was found in the P1 treatment, which was an average of 1.33 gr. The best feed conversion value is at P3 with a feed conversion value of 0.78 at a feeding dose of 5%. All treatments in this experiment gave 100% survival in comet fish (Carassius auratus) rearing. Maintenance of Comet Fish (Carassius auratus) seeds with takari feed in a recirculation system has a significant effect on absolute weight growth and specific growth.